Donald Trump’s Social Media Communication or the voice of a man is stronger than the voice of an institution - Tasente, Tanase; Rus, Mihaela (Technium Social Sciences Journal, 2019)
Social Media (Facebook, Instagram, Twitter, etc.) have revolutionized the communication strategies of public institutions in recent years, and communication strategies have understood the different principles on which these new media have been built, compared to traditional means of communication. Beyond the huge openness of these social environments, Social Meda is encouraging users to participate in the in the government process and created a new mechanism through which institution becomes a person, and institutional communication becomes interpersonal communication. This was speculated by many candidates who have won such a high online reputation that their voice can be stronger than the voice of an institution. This study focused on analyzing the Social Media communication strategy of Donald Trump, from 1 July 2018 to 1 July 2019. Thus, we have analyzed the Key Performance Indicators (KPIs) that facilitate Social Media communication, we have identified and analyzed the messages that generate high engagement from users as well as the dominant reactions generated by the online audience.